Location Conditions in East Germany and in Poland from the Point of View of the Companies - Tadeusz Baczko; Alexander Eickelpasch; Anna Lejpras; Andreas Stephan (Weekly Report, 2008)
A joint research project at the European University Viadrina, DIW Berlin and the Polish Academy of Science has investigated how companies assess their locational conditions and whether there is a relationship between location attributes and the company performance. In both countries the majority of companies assessed the same location attributes as being important or unimportant for the company's performance. Some remarkable differences were found in the evaluation of locational quality. In both countries, the supply of skilled employees is deemed to be the most important quality criterion of a location, and the current situation regarding this location factor is assessed as satisfactory. The companies in Poland more often evaluate the supply of training and qualification facilities as important compared to companies in East Germany, and the availability is assessed as good in both regions. Less important are traffic conditions. This is-not unexpectedly-assessed worse by Polish companies compared to the East German ones. The support by chambers of commerce is more often important for the Polish companies compared to East German ones. This potentially reflects the different importance of commercial authorities in both countries. Local administration is on average rated worse by the East German companies compared to Polish counterparts.
Keywords: L25; O31; R30; 330; Locational conditions; East Germany; Poland; Firm performance